Marketing Dreams, Manufacturing Heroes : The Transnational Labor Brokering of Filipino Workers - Guevarra, Anna Romina, 1973- (Book collections on Project MUSE., 2010)
In Marketing Dreams, Manufacturing Heroes Anna Romina Guevarra focuses on the Philippinesùwhich views itself as the "home of the great Filipino worker"ùand the multilevel brokering process that manages and sends workers worldwide. The experience of Filipino nurses and domestic workersùtwo of the country's prized exportsùis at the core of the research, which utilizes interviews with employees at labor brokering agencies, state officials from governmental organizations in the Philippines, and nurses working in the United States.